Teaching robotics systems in a multimedia environment - Freire, J. C.; Kina, R. B.; Neves, R. A.; de Lima, J. V. (Acta Press, 2004)
This paper describes the development of a multimedia educational system to teach and learn robotic systems. Multimedia resources have been used to build a virtual laboratory where users are able to utilize functions of a robotic arm, by moving and clicking the mouse without worrying about the detailed robot internal operation. The multimedia system is integrated with a real robotic arm, which was also developed at the university. Through robotic topic presentations and interactive capabilities provided by this system and its tools, students can devote themselves on the learning process just as they do in the traditional face-to-face classes. and the target public of this system are the engineering students themselves.
Keywords: teaching and learning systems; multimedia system; robotics; virtual system